Peran InstagraEFFECT OF INSTAGRAM, INFLUENCERS CREDIBILITY AND MOTIVATION TOWARDS DONATING BEHAVIORm, Kredibilitas Influencer dan Motivasi Individu pada Perilaku Mendonasi - Imas Permatasari; Zakaria Wahab; Marlina Widiyanti; Agustina Hanafi (Fakultas Ekonomi Universitas Negeri Jakarta, 2019)
The purposes of this study are to find empirical evidence by knowing: (1) The effect of Social Media Instagram towards Donating Behavior at Kitabisa platform, (2) The effect of Social Media Instagram towards Donating Behavior at Kitabisa platform with Influencer's Credibility as a moderating variable, and (3) The effect of Individual Motivation towards Donating Behavior at Kitabisa platform. It's causal research with 225 respondents using purposive sampling technique. The regression analysis program (Statistical Product and Service Solutions) is used to measure the relationship between variables. The results showed that there was a significant effect between Social Media Instagram and Individual Motivation towards Donating Behavior, and the addition of Influencer’s Credibility as moderating variable between Social Media Instagram and Donating Behavior showed an increased value, up to 3.8%.